The main factors that influence the public to pursue Islamic pawn broking (Ar-Rahnu) compare to the conventional pawn broking in Kuala Terengganu / Rubiah Abu Bakar ... [et al.] - Abu Bakar, Rubiah (2015)
This paper aimed to identify the vital factors that have contributed as the choice to the public to prefer Ar-Rahnu which is known to be Islamic pawn broking system popularly known to be one of the dominant pawn brokers in Malaysia. Realizing the need of Muslim community towards Islamic pawn broking, efforts were taken by certain authorities in making the Islamic approach in micro credit financing more feasible. Realizing the increasing popularity, relative usefulness and contribution of Islamic pawn broking as means for financial assistance, this paper proposed a comprehensive investigation by evaluating factors which influence the public to pursue the Islamic pawn broking (Ar Rahnu) compare to conventional pawn broking. Several identifiable variables were selected concerning storage charge, type of pawn item and customer service in measuring the main factors which influence the public to pursue the Islamic pawn broking (Ar-Rahnu) compare to conventional pawn broking. Using questionnaire as research instrument, 150 sets of questionnaires had been distributed to the customer at Ar-Rahnu MAIDAM Kuala Terengganu and other area in Kuala Terengganu. The result of the investigation demonstrated that all the identifiable constructs were substantial to very strong and significantly correlated with the main factors which influence the public to pursue the Islamic pawn broking (Ar Rahnu) compare to conventional pawn broking in Kuala Terengganu. The findings are symmetrical with the hypotheses formulated based on the previous studies and useful as one of the tools to strengthen the pawn broking system.